(untitled) (SAARC Journal of Agriculture, 2024)
Zeolites are crystalline aluminosilicates that exist naturally, and they are the most common mineral in sedimentary rocks. These minerals are called tectosilicates, and they have an open, three-dimensional structure with the cations required to maintain equilibrium of electrostatic charge between the aluminum framework and silicon tetrahedral units. Most common zeolites are chabazite, clinoptilolite, phillipsite, erionite, stilbite, heulandite, and mordenite. Zeolites are harmless for the environment and living things. Their multipurpose application in agriculture is mainly due to their high porosity, sorption-ion-exchange capability, and well-developed specific surface area. Applying zeolites directly to the soil improves its sorption capacity while simultaneously decreasing acidity and boosting nutrient uptake efficiency. Increased yields and less nutrient dispersion in the environment are achieved through better nitrogen utilization from fertilizers. This contributes to the closed-loop economy, the depletion of environmental resources, and the principles of sustainable development. Thus, zeolites have the potential to directly enhance agricultural environments. SAARC J. Agric., 22(1): 17-30 (2024)